Ethical Considerations in the Use of AI in Learning and Teaching for Special Education. - Noor Aida, Md Noor; Siti Noor Aneeis, Hashim; Juereanor, Mat Jusoh; Leha, Saliman; Shazali, Johari; NorHamidah, Ibrahim; Zaim Azizi, Abu Bakar; Mohd Norazmi, Nordin (Forester. Forester Communications Inc., 2026)
The rapid integration of Artificial Intelligence (AI) within the domain of Special Education (SPED) has catalyzed a paradigm shift in how students with diverse learning needs access curriculum and interact with their environment. While AI-driven tools—ranging from predictive text and speech-to-text systems to sophisticated social robots for neurodivergent learners—offer unprecedented levels of personalized support, they simultaneously introduce complex ethical quandaries. This paper critically examines the ethical landscape of AI in special education, focusing on four primary pillars: data privacy and the sensitivity of disability-related information, algorithmic bias and the risk of digital marginalization, the erosion of student autonomy, and the broadening digital divide. Through a qualitative analysis of current literature and existing policy frameworks, this study argues that the "technological fix" often overlooks the socio-ethical nuances of disability. The findings suggest that an "Ethics-by-Design" approach, grounded in Universal Design for Learning (UDL), is essential to ensure that AI serves as an instrument of empowerment rather than a mechanism for surveillance or exclusion. The paper concludes by proposing a set of normative guidelines for educators, developers, and policymakers to foster an inclusive and ethically sound AI-augmented learning ecosystem.